Analisis Kebijakan Dividen Terhadap Nilai Intrinsik dan Nilai Pasar Perusahaan - Muktiadji, Nusa; Felicia, Felicia (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Dividend policy is basically a company’s decision in determining how much net income wil be distributed to shareholders as dividend and how much will be retained. Dividend policy is able to influence intrinsic and market value of a company. In this study, the proxy of dividend policy is Dividend Pay-out (DPO) as independent variable and intrinsic value as dependent variable with indicator that is multiplication result of Earning Multiplier (EM) and Company Market Value obtained from stock price data of LQ45 at closing price. The purpose of this study is to identify the relationship between variables, the influence of independent variable to dependent variable, and finally to measure how significant the influence of variable X to variable Y will be, dividend policy to intrinsic and market value of the company. This case study was conducted at PT Aneka Tambang Tbk. and PT Timah Tbk., both are mining company. The results of this study are: 1) Dividend policy proxied by DPO has significant influence and relationship to the intrinsic value of PT Aneka tambang Tbk. But, at PT Timah Tbk., dividend policy to intrinsic value is not significant with alpha as high as 193.064, it’s due to the dividend policy does not influence the intrinsic value, but the intrinsic value is more influenced by EPS. 2) Dividend policy proxied by DPO has connection and fairly significant influence with the company’s market value at PT Aneka Tambang Tbk. But, at PT Tima Tbk., dividend policy to the company’s market value is not significant with alpha as high as 54.859, it’s due to the dividend policy does not influence the company’s market value, but the intrinsic value is influenced dominantly by the company’s market value. The result of the research shows that the dividend policy at PT Aneka Tambang Tbk has impact on intrinsic and market value better than the dividend policy has impact on intrinsic and market value at PT Timah Tbk. Keywords: dividend policy; intrinsic value; market value